Building Criteria for Temporary Quarantine Facilities During COVID-19 in Semarang City. Issue 1 (November 2021) - Murti Hari, R; Atmojo, P S; Abda, J; Fernando, R; Utama, A B; Taurano, G A; Hakim, F F; Friatmojo, E K
Abstract: The Covid-19 pandemic occurred suddenly and shocked the world in early 2020. However, this situation was exacerbated due to the unpreparedness of the government and local governments in dealing with it. Increasing readiness in prevention and handling is important in increasing regional preparedness to face pandemics. One of the efforts to increase readiness is by providing patient isolation and quarantine buildings, with the aim of controlling the spread of disease. However, it will be more efficient if a building is converted to an isolation and quarantine building during a pandemic. This study aims to identify the ideal criteria for isolation and quarantine for patients and suspects during a pandemic or epidemic. It is hoped that in the future, which buildings can be identified in the city of Semarang that have the potential to be converted into isolation and quarantine buildings. The research was conducted to determine the covid-19 quarantine facility considering the perceptions of experts who are skilled and have experience in the health sector. The variables used were location, accessibility, ventilation, basic functional infrastructure, space for facilities, recreation areas, and contact health monitoring areas. The method used in this research is a quantitative method using the Pairwise Comparison Analysis in Incomplete Analytic Hierarchy Process.